Athletes demonstrate an advantage in unconscious processing under working-memory load specifically within sport-related domains - Mao, Xuechen; Huang, Qin; Shi, Jilong; Yu, Yanglan; Li, Anmin (Frontiers in Psychology, 2025)
A growing body of evidence indicates that unconscious priming requires attentional resources, including high-level cognitive resources such as executive attention. However, the generalizability of this finding remains unexplored. Specifically, it remains unclear whether unconscious priming in skilled athletes, who are widely considered to possess advantages in unconscious processing, is limited by executive attention, and whether such advantages transfer to non-experiential domains remains debated. This investigation seeks to address this research gap through two dual-task experiments utilizing a mixed experimental design, attempting to elucidate the characteristics of unconscious priming under working-memory load in experienced athletes. One hundred and twelve participants, half of whom were elite table tennis athletes, completed a dual-task paradigm combining an N-back task with a masked priming task. In Experiment 1, the stimuli in the priming task were unrelated to sports scenarios, whereas in Experiment 2, they were sport-related. Mixed-effects ANOVAs, incorporating within-subject, between-subject factors and between-experiment factor, were conducted to analyze behavioral data. The results showed that in Experiment 2, athletes displayed a significantly larger unconscious priming effect under working-memory load compared to non-athletes (ηp2 = 0.08), whereas no such difference was observed in Experiment 1 (ηp2 = 0.13). Moreover, across both experiments, the unconscious priming effect in athletes was impaired with increased working-memory load (ηp2 = 0.17). Overall, these observations suggest that athletes excel in unconscious processing under working-memory load specifically in sports-related domains. Furthermore, athletes’ unconscious processing is limited by the available capacity of executive attention resources, which are occupied by increased working-memory load. Therefore, our study not only provides valuable insights into the boundary conditions of the athletes’ advantages in unconscious processing, but also extends extant frameworks of attention gating hypotheses of unconscious processing from non-athlete populations to elite athletes.